Psychosomatic mechanisms of emotional maladjustment in children with oncohematological diseases - Hura, Andrii; Abdriakhimova, Tsira (Psychosomatic Medicine and General Practice, 2025)
Oncohematological diseases in children represent not only a medical but also a profound psychosocial problem. Prolonged treatment, hospitalization, side effects of chemotherapy, and uncertainty of prognosis create a high level of chronic stress. This stress, in combination with biological and family-psychological factors, leads to the development of emotional maladaptation, manifested by anxiety, depressive symptoms, somatization, and behavioral disorders. Understanding the psychosomatic mechanisms of these processes is essential for the development of comprehensive psychocorrective care.